Our continent, our future African perspectives on structural adjustment - Mkandawire, P. Thandika (Trenton, NJ Africa World Press, 1999)
For decades now, many African countries have implemented the structural adjustment programs of the Bretton Woods Institutions. The results, however, have been less than sterling. Extreme poverty and underdevelopment continue to plague what is becoming the world's "forgotten continent," and it is now generally agreed that a new approach is urgently required. Our Continent, Our Future presents the emerging African perspective on this complex issue. The authors use as background their own extensive experience and a collection of 30 individual studies, 25 of which were from African economists, to summarize this African perspective and articulate a path for the future. They underscore the need to be sensitive to each country's unique history and current condition. They argue for a broader policy agenda and for a much more active role for the state within what is largely a market economy. Our Continent, Our Future is the very first publication to present the African perspective on the Bretton Woods approach to structural adjustment, and it does so with the input and support of top economists and scholars from every corner of Africa. This important book should be read by all people concerned with the future of Africa and issues of sustainable and equitable development.
Includes bibliographical references and index.
Keywords: Structural adjustment (Economic policy)--Africa.